DESIGN OF SPECIAL JUSTICE AGENCY ELECTION CHAIN IN INDONESIA - Tri Susilo (UNTAG Law Review, 2017)
Past-approval of government regulation in lieu of Law No.1 of 2014 concerning the election of governor, regent, and mayor (hereinafter called local election), In accordance with the decision of the Constitutional Court Number 97 /PUU-XI / 2013, the Constitutional Court is no longer authorized to resolve disputes on direct election results, because the provisions of Article 236C of Law Number 12 Year 2008 NRI are against the Constitution of 1945. Article 157 paragraph (1) Law No. 8 Year 2015 determines that the dispute settlement on direct election results become the authority of specialized judiciary. But before a specialized judiciary is formed, then the Constitutional Court is authorized to resolve disputes on direct election results. The authority of the Constitutional Court is the constitutional authority to fulfill temporary legal vacuum (rechtvakum). Therefore legislators should immediately establish a specialized judiciary which has the authority to resolve the disputes on direct election results. There is a new design in election mechanisms of regional hand. The law a quo stated that elections be held simultaneously at the national level. This design would require regulatory support, such as the establishment of as special court, solve any disputes that arise from the election. The problems emerge in this study is how the urgency of special court, how it compares to special court on election matters in various countries and how the relevance of the comparison can be applied in Indonesia. This was conducted using a legal-normative research. The research conclude unable to meet the demands for justice, for example, the court's decision are settled after the elections conducted and thick-layers on legal remedies so it is counterproductive to the election that have limited period of time. These legal remedies are even separated in several judicatures. Various countries have also established a special court on local elections with a variety of institutional design and procedural law. For Indonesia, the special court is ad hoc court, based on provincial and district or city and authorized to settle disputes concerning the local elections.